2017
DOI: 10.1039/c7nr03926c
|View full text |Cite
|
Sign up to set email alerts
|

Lipid nanodomains change ion channel function

Abstract: Signaling proteins and neurotransmitter receptors often associate with saturated chain and cholesterol-rich domains of cell membranes, also known as lipid rafts. The saturated chains and high cholesterol environment in lipid rafts can modulate protein function, but evidence for such modulation of ion channel function in lipid rafts is lacking. Here, using raft-forming model membrane systems containing cholesterol, we show that lipid lateral phase separation at the nanoscale level directly affects the dissociat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…Thus, such phase changes could affect ion channels which are sensitive to lipid composition. We recently demonstrated that gramicidin, a model ion channel, has a much shorter lifetime in the ordered phase of a lipid-raft mixture, and that phase mixing shifts the distribution of lifetimes (Weinrich et al, 2017). Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, such phase changes could affect ion channels which are sensitive to lipid composition. We recently demonstrated that gramicidin, a model ion channel, has a much shorter lifetime in the ordered phase of a lipid-raft mixture, and that phase mixing shifts the distribution of lifetimes (Weinrich et al, 2017). Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Conductance measurements were performed as described previously (59) For data analysis by Clampfit 10.3, no digital filtering was applied. Individual events of current blockages were discriminated and kinetic parameters were acquired by fitting logarithmic single, double, or triple exponentials to logarithmically binned histograms (60) as described previously (61). All lifetime histograms used 10 bins per decade.…”
Section: Expression and Purification Of Recombinantmentioning
confidence: 99%
“…30,32 These carotenoid-rich nanodomains in MLVs are instrumental in modulating membrane thermodynamics, which is parallel to lipid nanodomains in biological membranes, that are functional for facilitating membrane-associated cellular processes. 33,34 Polar carotenoids decrease fluidity and water permeability of the hydrophobic regions in lipid bilayers Membrane fluidity was probed at different regions of the lipid bilayer using Prodan and Laurdan, where Prodan probes at the headgroups (hydrophilic region) and Laurdan probes at the hydrophobic region given its longer hydrocarbon chain (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%